2006
DOI: 10.1186/1471-2415-6-35
|View full text |Cite
|
Sign up to set email alerts
|

A technique to train new oculomotor behavior in patients with central macular scotomas during reading related tasks using scanning laser ophthalmoscopy: immediate functional benefits and gains retention

Abstract: BackgroundReading with a central scotoma involves the use of preferred retinal loci (PRLs) that enable both letter resolution and global viewing of word. Spontaneously developed PRLs however often privilege spatial resolution and, as a result, visual span is commonly limited by the position of the scotoma. In this study we designed and performed the pilot trial of a training procedure aimed at modifying oculomotor behavior in subjects with central field loss. We use an additional fixation point which, when com… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
17
0
3

Year Published

2008
2008
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(24 citation statements)
references
References 27 publications
(29 reference statements)
2
17
0
3
Order By: Relevance
“…Moreover, our maturing population, with increasing rates of sight-threatening, age-related conditions, could compound issues with visual impairment and dysfunction secondary to brain injury [71], which can affect the patient more severely on the person level or functional vision level. It has already been shown that these expanding, age-related visually compromising conditions interface with rehabilitation [72–76], and these novel concepts [58,75,7780], as delineated previously, must account for and integrate these disorders into the framework to expand the knowledge base accordingly.…”
Section: Proposed Conceptual Model For Vision Rehabilitationmentioning
confidence: 99%
“…Moreover, our maturing population, with increasing rates of sight-threatening, age-related conditions, could compound issues with visual impairment and dysfunction secondary to brain injury [71], which can affect the patient more severely on the person level or functional vision level. It has already been shown that these expanding, age-related visually compromising conditions interface with rehabilitation [72–76], and these novel concepts [58,75,7780], as delineated previously, must account for and integrate these disorders into the framework to expand the knowledge base accordingly.…”
Section: Proposed Conceptual Model For Vision Rehabilitationmentioning
confidence: 99%
“…However, the effect of training on distance VA has received some attention. An increase in distance VA was reported in two small before and after studies ( n = 5 for each study), one randomised trial, and one case study . A change in distance VA was found in another small controlled before and after study, but this failed to reach significance when Bonferroni correction was applied for multiple comparisons .…”
Section: Resultsmentioning
confidence: 94%
“…A change in distance VA was found in another small controlled before and after study, but this failed to reach significance when Bonferroni correction was applied for multiple comparisons . In the earliest of these studies, Deruaz et al . reported a significant improvement ( p = 0.022) in distance VA after EV training administered using a scanning laser ophthalmoscope, although the improvements recorded for individual participants did not exceed the test‐retest repeatability.…”
Section: Resultsmentioning
confidence: 98%
See 1 more Smart Citation
“…The patient is still unable to perceive the location of his/her scotoma, but the examiner can coach the patient to move his/her eye to a more “optimal” location. 11,12 Use of these instruments has yet to become widely implemented in routine low vision evaluations, possibly because of their limited accessibility, high cost, increase in examination time, and the need for greater technical skill. Eccentric viewing training remains focused on helping the patient recognize where they have to look to perceive objects and perform visual tasks.…”
mentioning
confidence: 99%